Diversity and performance of eight new promising potato (Solanum tuberosum) genotypes in Garut District, West Java, Indonesia - Awang Maharijaya; Muhamad Syukur; Linda Nur Salma; Ulvi Levia Sanubary (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Maharijaya A, Syukur M, Salma LN, Sanubary UL. 2021. Diversity and performance of eight new promising potato (Solanum tuberosum L.) genotypes in Garut District, West Java, Indonesia. Biodiversitas 22: 2848-2858. Potato (Solanum tuberosum L.) is one of the main crops in the world. Potato consumption in Indonesia continues to increase, but the supply of potatoes cannot be fully met by domestic production. The low productivity of potatoes is due to the low quality. Efforts to increase potato production are by developing new varieties with higher yields. This study aimed to obtain information about the diversity and performance of eight IPB new potato genotypes in Garut District, West Java. The study used a randomized complete block design with a one-factor genotype and four replications. The characters observed included 46 characters consisting of 27 quantitative characters and 19 qualitative characters.The genotypes that was used as materials are PKHT-2019-010, PKHT-2019-011, PKHT-2019-012, PKHT-2019-013, PKHT-2019-014, PKHT-2019-015, PKHT-2019-016, PKHT-2019-017 and two varieties Medians and Intas as control. The result showed that the potato genotypes have a diversity of leaves, stems, flowers, and tubers. PKHT-2019-010, PKHT-2019-010, PKHT-2019-015, and PKHT-2019-017 have higher productivity than Medians and Intan as control. PKHT-2019-012 productivity was not significantly different from Intan as control. The genotypes that had a higher or were the same productivity as the control varieties might be the expected genotypes that can be developed as new varieties. The genotypes expected to be developed are PKHT-2019-015, PKHT-2019-010, PKHT-2019-017, and PKHT-2019-012